RESOCIALIZATION OF ADOLESCENTS ON PROBATION: PSYCHOSOCIAL APPROACH WITH ELEMENTS OF COACHING - Inesa Harkusha; Serhii Dubinskyi (Alfred Nobel University Journal of Pedagogy and Psychology)
The article discusses current approaches to the resocialization of adolescents on probation in the con- text of psychosocial support. The purpose of the article is to identify the specific features of the resocialisation of conditionally sen- tenced adolescents in the context of psychosocial support, in particular through the integration of coaching- based elements as a factor in enhancing the effectiveness of rehabilitation programmes. The study employed methods of retrospective and categorical analysis of primary sources and aca- demic literature, as well as techniques of analogy, comparison, and generalisation. Modern models of probation are analysed, the peculiarities of working with adolescents who are registered are determined, and the expediency of integrating coaching elements into the resocialization process is substantiated. The importance of forming intrinsic motivation, responsibility and self-regulation skills in adolescents through a coaching approach as an effective complement to traditional methods of psy- chological influence is emphasized. It is noted that in many countries, approaches to working with juvenile offenders are being rethought. Traditional methods of resocialization are complemented by innovative psychosocial tools aimed not only at controlling, but also at developing the personal potential of an adolescent. Based on the analysis of primary sources, it is established that macro-social factors of children’s delin- quent behaviour have a negative impact on minors and do not directly lead to their committing illegal acts. They are mediated by the adolescent’s immediate environment and manifest themselves as family and per- sonal problems. A crime can be a way of overcoming problems caused by social factors and a reaction to frustration caused by the inability to overcome them in other ways. It is noted that some countries have special closed institutions for juvenile offenders (USA, Canada, France). In modern criminal law of different countries, resocialization of convicts is considered as a key ele- ment of the penitentiary system. It is stated that the legislation of some countries does not explicitly provide for the term “resocializa- tion”, but its content is implicitly present in the general policy of the State on the treatment of offenders. Modern models of resocialization are closely related to the penitentiary system, but differ in the degree of integration and interaction with it. It is determined that the forms of educational and upbringing work with young people, as well as the nature of deviant behaviour, largely depend on the type of institution that performs an educational or pre- ventive function. In the context of modern approaches and individualized models to the resocialization of minors, the introduction of coaching approaches is becoming increasingly relevant. It is determined that coaching, as a form of psychological assistance in the educational and social en- vironment, contributes to the formation of young people’s ability to self-development, autonomy, internal responsibility and positive self-esteem. It has been concluded that the use of the coaching approach as a tool for developing intrinsic motiva- tion, responsibility and self-regulation skills in persons in conflict with the law is particularly promising. The combination of preventive experience, educational initiatives, and coaching strategies creates potential for the humanisation of resocialisation approaches in Ukraine and for the development of an environment con- ducive to the positive behavioural transformation of juvenile offenders.